Potential Risk Factors for Mortality Due to Cardiovascular Disease Among Hemodialysed Patients in Indonesia - Ramatillah, Diana Laila; Syed Sulaiman, Syed Azhar; Khan, Kashif Ullah (UI Scholars Hub, 2020)
Severe vascular calcifications, alterations in cardiovascular structure and function, immune dysfunction, and anemia are adverse effects of parathyroid hormone (PTH), which may contribute to increase risk factors of cardiovascular morbidity and mortality among renal failure patients. To evaluate the potential risk factors for mortality due to cardiovascular disease among hemodialysed patients in Indonesia, this cohort study was conducted. This study included 178 patients on hemodialysis who had been followed up two times a week for nine months (prospective cohort) and 185 patients who died in the last five years (retrospective cohort). Universal sampling technique were used to select the study subjects. Male was prevalence among hemodialysed patients in hemodialysis center, Jakarta, Indonesia and the third group of age (51-60 years) was predominant among these patients. Java ethnicity was found in almost 50% hemodialysed patients in this hemodialysis center. Most of those patients had hypertensive family history. Besides that, more than 70 percent of them were married and non-smoker. The study found that cardiovascular disease caused mortality among hemodialysed patients in Indonesia and the duration of cardiovascular disease influenced the probability of death/risk of mortality among these patients (HR 2.39, p = 0.006). Mortality among patients on hemodialysis in this study was caused by cardiovascular disease, and this cause of death was included in one of the biggest causes. During the study, several practice patterns revealed no PTH level check, no patients got calcimimetic agents such as rocalcitriol/calcitriol and calcium value check was conducted irregularly. As we know, there is a correlation between PTH, calcium and cardiovascular disease. Hence, mortality due to cardiovascular disease among hemodialysed patients significantly correlated with the duration of cardiovascular disease, and potentially with lack of PTH check, calcium check and rocalcitriol/calcitriol supplement given to those patients.